2012
DOI: 10.48550/arxiv.1207.6212
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precise Radial Velocities of 2046 Nearby FGKM Stars and 131 Standards

C. Chubak,
G. Marcy,
D. A. Fischer
et al.

Abstract: We present radial velocities with an accuracy of 0.1 km s −1 for 2046 stars of spectral type F,G,K, and M, based on ∼29000 spectra taken with the Keck I telescope. We also present 131 FGKM standard stars, all of which exhibit constant radial velocity for at least 10 years, with an RMS less than 0.03 km s −1 . All velocities are measured relative to the solar system barycenter. Spectra of the Sun and of asteroids pin the zero-point of our velocities, yielding a velocity accuracy of 0.01 km s −1 for G2V stars. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(97 citation statements)
references
References 24 publications
7
89
1
Order By: Relevance
“…We derived radial velocities by cross-correlating our spectra with a template spectrum of the metal-poor giant HD122563 that was obtained on the second night of data collection. The rest velocity of HD122563 was assumed to be −26.51 km s −1 (Chubak et al 2012), and the cross-correlation was performed over the Mg b absorption region (4900 Å to 5400 Å). We further performed a cross-correlation over the Telluric A-band absorption region (7590 Å to 7710 Å) between our spectra and a template spectrum of the hot, rapidly rotating giant HR4781 to correct for any slit mis-centering.…”
Section: Radial Velocity Measurementsmentioning
confidence: 99%
“…We derived radial velocities by cross-correlating our spectra with a template spectrum of the metal-poor giant HD122563 that was obtained on the second night of data collection. The rest velocity of HD122563 was assumed to be −26.51 km s −1 (Chubak et al 2012), and the cross-correlation was performed over the Mg b absorption region (4900 Å to 5400 Å). We further performed a cross-correlation over the Telluric A-band absorption region (7590 Å to 7710 Å) between our spectra and a template spectrum of the hot, rapidly rotating giant HR4781 to correct for any slit mis-centering.…”
Section: Radial Velocity Measurementsmentioning
confidence: 99%
“…Signal to noise ratios (SNR) per pixel of the final reduced spectra at 4100 Å and 5500 Å are listed in Table 1. Heliocentric radial velocities of the stars were determined by cross-correlation (Tonry & Davis 1979) of the target spectra with a spectrum of the radial-velocity stan-dard star HD122563 (V hel = −26.51 km s −1 ; Chubak et al (2012)) obtained with the same instrument setup as the target stars. Depending on the SNR of the target spectra, 30 to 50 individual orders were used for the cross-correlation.…”
Section: Observationsmentioning
confidence: 99%
“…These measurements and their corresponding uncertainties are given the symbols v t and σ vt , respectively. These RVs were calculated following the methodology of Chubak et al (2012). They 4.07 ± 0.10 V sin i (km s −1 ) 3.29 ± 1.0…”
Section: Application Of the Matched-template Technique To Kic 5951458mentioning
confidence: 99%
“…These individual measurements are yet unpublished, but the Gaia Data Release 2 included their median value (−23.0 ± 1.3 km s −1 ) and the corresponding epoch (2015.5 or BJD = 2457204.5). This Gaia RV can be compared to the telluric-calibrated, absolute RVs produced from the HIRES spectra by the methodology of Chubak et al (2012), which we list in Table 4. Using standard stars, Soubiran et al (2018) found excellent agreement between the Gaia RVs and the catalog of Chubak et al (2012), quantified by a dispersion of only 0.072 km s −1 , which is much lower than the error on the Gaia RV measurement of KIC 5951458.…”
Section: The Long-term Rv Trendmentioning
confidence: 99%
See 1 more Smart Citation